Facies Analysis, Sedimentology and Petrographic studies of the Eocene Ameki Formation, SE Nigeria - C.K, Ndeze; A.U, Okoro; K. A., Haruna; C.G, Kalu; O.O, Afolayan; O.O, Afolayan (International Journal of Advanced Geosciences, 2021)
Detailed sedimentology and petrographic studies of outcrop sections of the Eocene Ameki formation exposed in the Northern depobelts of the Niger Delta was done to, characterize the sediment facies, determine the depositional environment and also to development a depositional model for the study area. Three facies associations were have been identified in the study area based on lithology, primary sedimentary structures, fossil content, geometry, lateral and vertical succession of beds and the nature of bedding contacts,and they include; brackish swamp, braided fluvial channels and Tidal creek environments. Results from polished section study showed the percentage distribution of the maceral groups as Huminite = 58.25%, Liptinite = 34.35%, Inertinite = 7.5%. The lignites are mainly Duroclarite in nature, deposited in swamp vegetation with preserved cell structures in a slightly oxic to anoxic condition. Furthermore results from petrographic studies of representative sandstone samples showed that the predominant mineral is quartz with a greater number of them showing Monocrystalline features, while the feldspars are mostly of the plagioclase type. Ternary diagram plots for the sandstones suggest a subarkose to lithic subarkose, and Arkose to lithicarkose for the sandstones, a mixed provenance of plutonic, metamorphic and recycled sedimentary sources which are consistent with humid climatic conditions.Â Â Â Â